Peranan Akhlaq Islami dalam Pembentukan Legislasi yang Berkeadilan: Akhlaq Islami dan Legislasi Berkeadilan - Zamzami; Budianto, Tenda (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
This research delves into the crucial role of Islamic morals (Akhlaq Islami) in the legislative process aimed at creating justice in society. The concept of Akhlaq Islami serves as a moral foundation that guides the creation of fair and inclusive laws. This study highlights the importance of values such as honesty, justice, and empathy in the legislative process. By analyzing the cultural and social context of Indonesia, this research identifies how Islamic moral values are reflected in the national legal framework. The study illustrates that the role of Akhlaq Islami in forming just legislation has a significant impact both in the context of Indonesia and globally. Various findings and analyses show that Islamic moral values, such as justice, equality, and humanity, have a strong influence on the policymaking and legislative process. However, the implementation of Akhlaq Islami values still faces several challenges, including discrepancies between Islamic moral principles and the complex political and social realities. Keywords: Islamic Ethics, Legislation, Justice, Culture, and Social